Cytokine induced killer cells-assisted delivery of chlorin e6 mediated self-assembled gold nanoclusters to tumors for imaging and immuno-photodynamic therapy. (July 2018) - Xia, Fangfang; Hou, Wenxiu; Liu, Yanlei; Wang, Wentao; Han, Yu; Yang, Meng; Zhi, Xiao; Li, Chenlu; Qi, Daizong; Li, Tianliang; Martinez de la Fuente, Jesus; Zhang, Chunlei; et al.
Abstract: The cytotoxicity and unique tumor-tropic properties of cytokine-induced killer (CIK) cells render them promising in the field of cancer immunotherapy and delivery systems. Here, we report a novel and facile approach to assemble gold nanoclusters (GNCs) into stable and monodispersed nanoparticles (NPs) using Chlorin e6 (Ce6) molecules. Notably, the fluorescence intensity of the GNCs-Ce6 NPs was about 4.5 folds stronger than the GNCs counterparts. The as-prepared GNCs-Ce6 NPs were conjugated with CD3 antibody (Ab) and further employed to label CIK cells to create a CIK cell-based drug delivery system (Ce6-GNCs-Ab-CIK). The Ce6-GNCs-Ab-CIK exhibited high tumor-targeting efficiency and excellent therapeutic efficacy toward MGC-803 tumor-bearing mice. Benefiting from the synergistic therapeutic effect between GNCs-Ce6-Ab NPs and CIK cells, the GNCs-Ce6-Ab-CIK strategy may present an ideal cancer theranostic platform for tumor targeted imaging and combination therapy.